Correlation between rheological propertiesm and limonene release in pectin gels using an electronic nose - Monge, Maria Eugenia (2008)
Pectin gels at different polymer concentrations were used as matrices for the encapsulation of a volatile flavour (limonene). This provides a useful model system for studying the influence of the matrix viscoelastic properties on the flavour release towards the gel headspace. The electronic nose technique and principal component analysis (PCA), a multivariate data analysis, were used for detecting changes in the fingerprint of the released vapour as a function of pectin concentration. Samples with different composition were also studied by rheological measurements in order to discriminate the effects of polymer concentration on the gelation kinetics from those due to the addition of limonene and the detergent used to dissolve it. The combined approach, rheometry-electronic nose, allows obtaining a direct semi-quantitative correlation between the expected decrease of flavour release intensity and the increasing solid like character of the matrix due to trapping effect. In fact, the comparison of the viscoelastic properties for matrixes with and without the flavour, together with direct observation by optical microscopy, suggests that the release modulation is mainly due to interaction of the gelling pectin with the microemulsion of detergent and flavour.